Concurrent effect of Alfven waves and planar magnetic structure on geomagnetic storms - Shaikh, Zubair I.; Raghav, Anil; Vichare, Geeta; Bhaskar, Ankush; Mishra, Wageesh; Choraghe, Komal (My University, 2019)
Generally, interplanetary coronal mass ejection (ICME) triggers intense and strong geomagnetic storms. It has been established that the ICME sheath-moulded planar magnetic structure enhances the amplitude of the storms. Alfven waves embedded in ICME magnetic clouds or high solar streams including corotating interacting regions (CIRs) in turn extend the recovery phase of the storm. Here, we investigate a geomagnetic storm with a very complex temporal profile with multiple decreasing and recovery phases. We examine the role of planar magnetic structure (PMS) and Alfven waves in the various phases of the storm. We find that fast decrease and fast recovery phases are evident during transit of PMS regions, whereas a slight decrease or recovery is found during the transit of regions embedded with Alfvenic fluctuations.
Keywords: Magnetic reconnection and the sun; Coronal mass ejections (CMEs); Magnetic fields and solar wind; Solar winds; Sun